The turtle of Michigan - Nye, Naomi Shihab (Greenwillow Books, 2022)
Eight-year-old Aref is excited to reunite with his father in Ann Arbor, Michigan where he will start a new school, and while Aref misses his grandfather, his Sidi, he knows that his home in Oman will always be waiting for him.